Aryl and heteroaryl N-[4-[4-(2, 3-substituted-phenyl)piperazine-1-yl]alkyl]carbamates with improved physico-chemical properties as dual modulators of dopamine D3 receptor and fatty acid amide hydrolase12. Issue 3 (17th February 2016) - Micoli, A.; De Simone, A.; Russo, D.; Ottonello, G.; Colombano, G.; Ruda, G. F.; Bandiera, T.; Cavalli, A.; Bottegoni, G.
Abstract : Improving the physico-chemical profile of a MTDL series. Abstract : With respect to one-target molecules, multi-target-directed ligands have the potential to obtain a synergistic therapeutic effect while eliciting more manageable side effects. Within this framework, we have recently reported the first class of multi-target compounds endowed with activity toward dopamine D3 receptor and human fatty acid amide hydrolase, targets that have been independently investigated in the treatment on nicotine addiction. The main limitation of these derivatives is poor water solubility, a drawback strongly hampering the development of this class. Here we synthesized and tested different aryl and heteroaryl N -[4-[4-(2, 3-substituted-phenyl)piperazine-1-yl]alkyl]carbamates aiming at identifying compounds maintaining good activity at the main targets and selectivity toward the investigated off targets while displaying an improved physico-chemical profile.